Respuesta :

Answer:

The answer to your question is: the third option

Step-by-step explanation:

              x² + 5x = - 1

              x² + 5x + [tex](\frac{5}{2}) ^{2}[/tex] = -1  + [tex](\frac{5}{2} )^{2}[/tex]

             (x + [tex]\frac{5}{2}[/tex])² =   - 1 + 25/4

            (x + [tex]\frac{5}{2}[/tex])²  =  (-4 + 25) / 4

            (x + [tex]\frac{5}{2}[/tex])² = 21/4

            (x + [tex]\frac{5}{2}[/tex]) = ± [tex]\sqrt{\frac{21}{4} }[/tex]

            x = [tex]\frac{5}{2} ±   \frac{\sqrt{21}}{2}[/tex]

            x = [tex]\frac{-5 ± \sqrt{21} }{2}[/tex]